Ceramide Remodeling and Risk of Cardiovascular Events and Mortality - Peterson, Linda R.; Xanthakis, Vanessa; Duncan, Meredith S.; Gross, Stefan; Friedrich, Nele; Völzke, Henry; Felix, Stephan B.; Jiang, Hui; Sidhu, Rohini; Nauck, Matthias; Jiang, Xuntian; Ory, Daniel S.; et al. (Journal of the American Heart Association, 2018)
Background Recent studies suggest that circulating concentrations of specific ceramide species may be associated with coronary risk and mortality. We sought to determine the relations between the most abundant plasma ceramide species of differing acyl chain lengths and the risk of coronary heart disease (CHD) and mortality in community‐based samples. Methods and Results We developed a liquid chromatography/mass spectrometry assay to quantify plasma C24:0, C22:0, and C16:0 ceramides and ratios of these very–long‐chain/long‐chain ceramides in 2642 FHS (Framingham Heart Study) participants and in 3134 SHIP (Study of Health in Pomerania) participants. Over a mean follow‐up of 6 years in FHS, there were 88 CHD and 90 heart failure (HF) events and 239 deaths. Over a median follow‐up time in SHIP of 5.75 years for CHD and HF and 8.24 years for mortality, there were 209 CHD and 146 HF events and 377 deaths. In meta‐analysis of the 2 cohorts and adjusting for standard CHD risk factors, C24:0/C16:0 ceramide ratios were inversely associated with incident CHD (hazard ratio per average SD increment, 0.79; 95% confidence interval, 0.71–0.89; P<0.0001) and inversely associated with incident HF (hazard ratio, 0.78; 95% confidence interval, 0.61–1.00; P=0.046). Moreover, the C24:0/C16:0 and C22:0/C16:0 ceramide ratios were inversely associated with all‐cause mortality (C24:0/C16:0: hazard ratio, 0.60; 95% confidence interval, 0.56–0.65; P<0.0001; C22:0/C16:0: hazard ratio, 0.65; 95% confidence interval, 0.60–0.70; P<0.0001). Conclusions The ratio of C24:0/C16:0 ceramides in blood may be a valuable new biomarker of CHD risk, HF risk, and all‐cause mortality in the community.